2020
DOI: 10.3390/nu13010062
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Dietary Oxalate and Oxalate Precursors to Urinary Oxalate Excretion

Abstract: Kidney stone disease is increasing in prevalence, and the most common stone composition is calcium oxalate. Dietary oxalate intake and endogenous production of oxalate are important in the pathophysiology of calcium oxalate stone disease. The impact of dietary oxalate intake on urinary oxalate excretion and kidney stone disease risk has been assessed through large cohort studies as well as smaller studies with dietary control. Net gastrointestinal oxalate absorption influences urinary oxalate excretion. Oxalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 112 publications
0
44
0
1
Order By: Relevance
“…The decrease of oxalic acid may indicate that the metabolism of ascorbic acid is affected, which aggravates oxidative stress in the body and promotes inflamm-aging [ 68 ]. In addition, recent studies have shown that gut microbes play an important role in the metabolism of oxalic acid [ 69 , 70 ]. Many microbiota, such as Oxalobacter formigenes, Lactobacilli, and Bifidobacteria, are involved in the degradation of oxalic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of oxalic acid may indicate that the metabolism of ascorbic acid is affected, which aggravates oxidative stress in the body and promotes inflamm-aging [ 68 ]. In addition, recent studies have shown that gut microbes play an important role in the metabolism of oxalic acid [ 69 , 70 ]. Many microbiota, such as Oxalobacter formigenes, Lactobacilli, and Bifidobacteria, are involved in the degradation of oxalic acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective cohort study reported only a modest positive association between dietary oxalate intake and the risk for incident stone formation [139]. Several reasons could be responsible for these inconsistencies, including the use of food frequency questionnaires, which are prone to errors, to evaluate dietary oxalate intake in large cohort studies, the daily variation in the oxalate ingestion and the variability of the oxalate content due to growth conditions, preparation and processing of food [59,[140][141][142]. Therefore, studies using diets strictly controlled in their oxalate and nutrient content and the use of comprehensive data on the oxalate content of raw and processed foods are required.…”
Section: Oxalatementioning
confidence: 99%
“…Studies in healthy subjects, patients with kidney stones or with PH have been performed and favor a variable level of renal oxalate secretion [ 5 , 6 ]. In healthy subjects, gut secretion of oxalate plays little role in the excretion of oxalate (<5%) [ 7 ]. There have been suggestions that the excretion of oxalate is increased in PH1, but definitive evidence is difficult to obtain, in part due to the difficulties in accurate measurements of low levels of oxalate, notably in plasma, tissues and feces [ 6 , 8 ].…”
Section: Oxalate and Ph1mentioning
confidence: 99%